Impact of delays in definitive treatment on overall survival: a National Cancer Database study of patients with Hodgkin lymphoma. Issue 5 (3rd May 2016) - Parikh, Rahul R.; Grossbard, Michael. L.; Harrison, Louis. B.; Yahalom, Joachim
Abstract: The purpose of this large observational study was to examine outcomes in patients with Hodgkin lymphoma (HL) by timing to definitive chemotherapy (TTC) using standard and propensity score (PS)-adjusted Cox proportional hazards models. From 1998–2011, 56, 457 patients with stage I–IV HL were studied, with a median follow-up of 6.0 years (median age = 39). Median TTC was 26 days from diagnosis. The cohort of "early" (<60 days from diagnosis) TTC patients included 45, 307 (80.3%) patients and "late" (≥60 days) TTC was 11, 150 (19.7%). Patients were more likely to experience early TTC if they were of a younger age, at an advanced stage, with "B" symptoms, favorably insured, favorable socioeconomic status, and treated at comprehensive cancer center (all p  < 0.05). Ten-year overall survival for patients with early TTC was 73.2% vs. 70.0% for those with late TTC (HR = 0.87; 95%CI, 0.83–0.92, p  < 0.0001). After PS-matching for co-variates, early TTC was not associated with overall survival (HR = 0.96; 95%CI, 0.85–1.08, p = 0.51). This represents the only study to evaluate overall survival by time to definitive treatment for HL